A development cooperation Erasmus Mundus partnership for capacity building in earthquake mitigation science and higher education - Faggella, M. (2012)
Successful practices have shown that a community’s capacity to manage and reduce its seismic risk relies on capitalization on policies, on technology and research results. An important role is played by education, than contribute to strengthening technical curricula of future practitioners and researchers through university and higher education programs. EUNICE is a European Commission funded higher education partnership for international development cooperation with the objective to build capacity of individuals who will operate at institutions located in seismic prone Asian Countries. The project involves five European Universities, eight Asian universities and four associations and NGOs active in advanced research on seismic mitigation, disaster risk management and international development. The project consists of a comprehensive mobility scheme open to nationals from Afghanistan, Bangladesh, China, Nepal, Pakistan, Thailand, Bhutan, India, Indonesia, Malaysia, Maldives, North Korea, Philippines, and Sri Lanka who plan to enroll in school or conduct research at one of five European partner universities in Italy, Greece and Portugal. During the 2010-14 time span a total number of 104 mobilities are being involved in scientific activities at the undergraduate, masters, PhD, postdoctoral and academic-staff exchange levels. Researchers, future policymakers and practitioners build up their curricula over a range of disciplines in the fields of earthquake engineering, seismology, disaster risk management and urban planning.